Free will - Balaguer, Mark (Cambridge, MA : MIT Press, 2014)
A philosopher considers whether the scientific and philosophical arguments against free will are reason enough to give up our belief in it.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Free will and determinism; PHILOSOPHY -- Free Will & Determinism; Free will and determinism; Electronic books